2023
DOI: 10.1108/ijoem-06-2022-0976
|View full text |Cite
|
Sign up to set email alerts
|

Corporate net working capital: evidence from Shariah compliance

Abdullah Bugshan,
Faisal Alnori,
Husam Ananzeh

Abstract: PurposeThis paper examines the influence of Shariah compliance (SC) on firms' net working capital (NWC) target and adjustment speed.Design/methodology/approach The study samples of non-financial firms taken from six Gulf Cooperation countries between 2005 and 2019 and employs static and dynamic models to answer the present study research questions.FindingsThe outcomes of the study indicate that SC is one of the major determinants of the decision made by the corporation regarding their NWC. More specifically, e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…This implies that firms issue less long-term debt when interest rates increase, to avoid the higher cost associated with long-term debt financing. Therefore, during times of high interest rates, firms will rely less on long-term debt and use internal financing more likely (Bugshan et al, 2023;Nguyen, 2022;Alnori & Alqhtani, 2019). Table 4 summarizes the OLS regression analysis examining the factors influencing debt maturity (DM).…”
Section: Regression Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This implies that firms issue less long-term debt when interest rates increase, to avoid the higher cost associated with long-term debt financing. Therefore, during times of high interest rates, firms will rely less on long-term debt and use internal financing more likely (Bugshan et al, 2023;Nguyen, 2022;Alnori & Alqhtani, 2019). Table 4 summarizes the OLS regression analysis examining the factors influencing debt maturity (DM).…”
Section: Regression Resultsmentioning
confidence: 99%
“…The descriptive statistics show that the mean and median values for assets tangibility (Tang) are .40 and .37 respectively, while the mean and median values for corporate liquidity (liquid) are 2.81 and 1.71 respectively. The mean values for the variable liquidity reveal that, on average, Saudi firms own current assets 2.8 times more than their current liabilities to cover their current obligation and working capital needs, which indicates that Saudi firms seem to have no liquidity issues in the short-term (Bugshan et al, 2023). Further, the mean values of assets maturity (AM) and growth opportunities (Growth) are 4.11 and 0.147.…”
Section: 1mentioning
confidence: 97%
“…Here, WCM is defined as our dependent variable. By reviewing the existing literature, it can be found that various researchers have used the cash conversion cycle (CCC) (Nobanee et al 2011;Amponsah-Kwatiah and Asiamah 2021;Sawarni et al 2023;Rahman et al 2024), net working capital (NWC) (El-Ansary and Al-Gazzar 2021; Bugshan et al 2023;Sargon 2024), receivables and inventory turnover (Knauer and Wöhrmann 2013;Zimon et al 2024), liabilities turnover Kouaib and Bu Haya 2024), and other important ratios as a measure for evaluating working capital management (WCM). The noteworthy point is that repetitive use of a few proxies for WCM in most prior studies have been identified (Prasad et al 2019).…”
Section: Research Model and Variablesmentioning
confidence: 99%